Asprosin, irisin, and meteorin-like protein immunoreactivity in different stages of colorectal adenocarcinoma - Uzun, Mehmet; Ilhan, Yavuz Selim; Bozdag, Ahmet; Yilmaz, Mustafa; Artas, Gokhan; Kuloglu, Tuncay (Elsevier Gmbh, 2023)
Objective: In this study, we aimed to investigate the immunoreactivity of asprosin, irisin, and meteorin-like protein (METRNL) in different stages of colorectal adenocarcinoma, which is the most common malignancy of the gastrointestinal tract. Materials and methods: Overall, 60 patients with colorectal adenocarcinoma, including 20 well (Group 1), moderately (Group 2), and poorly differentiated (Group 3) cases, respectively, and 20 with normal colonic mucosa, were examined using light microscopy for immunohistochemical staining of asprosin, METRNL, and irisin. Results: Compared with the control group, a significant increase in irisin and asprosin immunoreactivity was found in the grade 1 and 2 colorectal adenocarcinoma groups. Moreover, compared with the grade 1 and 2 groups, this immunoreactivity was significantly decreased in the grade 3 colorectal adenocarcinoma group. Although there was no significant difference in METRNL immunoreactivity between the grade 1 and control groups, a statistically significant increase in this immunoreactivity was found in the grade 2 group. In contrast, METRNL immunoreactivity was significantly decreased in the grade 3 group compared with the grade 2 group. Conclusion: We found that in early-stage colorectal adenocarcinoma there was an increase in the immunoreactivity of asprosin and irisin, but in the advanced stage there was a decrease in immunoreactivity. Although METRNL immunoreactivity did not change in the control and grade 1 groups, it was found to increase significantly in the grade 2 group and decrease in the grade 3 group.
Keywords: Adenocarcinoma; Asprosin; Colon; Irisin; Meteorin-like Protein